Step by Step Instructions to Utilize Gagne's Model of Instructional Outline in Educating Psychomotor Aptitudes - Khan, Danish Ali; Wahid, Iqbal; Zeb, Sultan (International Journal of Pathology, 2018)
Abstract: Gagne's nine steps is an instructional framework to achieve better learning results, Applying Gagne'snine steps model is a superb method to guarantee a successful and methodical learning program as it offersstructure to the lesson designs and encompassing all prospects to education. Simulators fall into the broad contextof simulation-based medical education (SBME). It uses simulative guides with a specific end goal to upgrade theinstructive message by reenacting the clinical situation. Reenactment gadgets fill in as a contrasting option to thegenuine patient and allow teachers to increase full control of a pre-chosen clinical scene without the danger ofupsetting patients or experiencing other unsafe part of learning on genuine patients. It isn't contrasting option tobedside educating but instead correlative expansion. It became an integral part of the medical curriculum, acrossall medical professions and throughout medical careers. It will be incorporated as the leading standardizedperformance assessment method of health professional’s competencies